Exclusive Use of Air as Gas Tamponade in Rhegmatogenous Retinal Detachment - Kang Yeun Pak; Seok Jae Lee; Han Jo Kwon; Sung Who Park; Ik Soo Byon; Ji Eun Lee (Journal of Ophthalmology)
Purpose. To investigate outcomes of vitrectomy for rhegmatogenous retinal detachment (RRD) using air exclusively as the gas tamponade. Methods. This retrospective, interventional, consecutive case series involved reviewing medical records of patients that underwent vitrectomy and gas tamponade for RRD between January 2013 and December 2015. Patients whose eyes were treated exclusively with air tamponade since July 2014 were assigned to the air group, while those treated with heterogeneous gas agents before June 2014 were assigned to the control group. The primary outcome was the primary reattachment rate. Best-corrected visual acuity (BCVA) and duration to detect redetachments were assigned as the secondary outcomes. Results. The air group and the control group included 71 and 72 eyes, respectively. The primary reattachment rate was 94.4% in the air group and there was no significant difference with 94.4% in the control group (p=0.951). BCVA was significantly better in the air group at 1 month (p=0.021) but not at 3 months postoperatively (p=0.561). Redetachments were recognized earlier in the air group (9.3 ± 0.5 days) compared with those in the control group (21.3 ± 7.4 days) (p=0.041). Conclusions. In cases of simple RRD with sufficient removal of subretinal fluid, air could be considered for use as gas tamponade. This trial is registered with KCT0002358.